Karakteristik Pupuk Slow Release Berbasis Biochar Tongkol Jagung yang Diperkaya Nutrisi - Nita, Ayu; Sukmawati; Rahim, Iradhatullah; Suherman; Qadri, Sri Nur; Zamzam, Syamsiar; Noerfitryani; MK, Pratiwi (Jurnal Galung Tropika, 2025)
This research aims to determine the characteristics of slow-release fertilizer based on corncob biochar which is enriched with various nutrient sources (NPK, SP36, cow urine and Azotobacter). Research methods include making biochar through pyrolysis and nutrient impregnation. Fertilizer characterization includes analysis of nutrients, material fractions, biochar stability, and functional groups using spectra (FTIR). The results of the four analyzes carried out showed that the SRFbiochar+SP36+cow urine formulation provided the best results in retaining nutrients and water.  The nutrient content produced by SRFbiochar+SP36+cow urine, namely N(0.35%) P (0.63%), K (0.7%), Corganic (6.49%), volatile content (15%) strengthened by the ultimate results which show high nutrient content (C=10.09%, N=0.35%), which is explained by the formation of hydroxy functional groups (O-H) in tire 3444.87 and carboxy groups on the band 1635.64. These results indicate that the SRF-BiocharSP36+bovine urine formulation has the potential to be developed as a slow-release fertilizer to increase fertilization efficiency in dry land for sustainable soil fertility improvement.